2015
DOI: 10.1111/apm.12365
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant of IL28B rs12979860, as predictive marker of interferon‐based therapy in Pakistani population

Abstract: Hepatitis C virus (HCV) genotypes and genetic variants of interleukin 28B (IL28B) are significantly associated with interferon plus ribavirin treatment of HCV infection. We investigated the distribution of HCV genotypes and single-nucleotide polymorphisms (SNPs) of IL28B (rs12979860 and rs8099917) in Pakistani population. IL28B genotyping was performed by allele-specific PCR and restriction fragment length polymorphism PCR in 140 chronic hepatitis C patients (CHC) and 120 healthy controls. HCV genotype 3 (HCVG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Relating to our previously published study HCV genotypes and IL28B rs12979860 SNP found among the Pakistani HCV patients as predictive markers for the efficiency of (IFN + ribavirin) combinational therapy. The results of this study were found consistent with the study published recently, which reports that IL28B contributes to viral resistance and is known to be up regulated as a result of interferons and RNA virus infection .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Relating to our previously published study HCV genotypes and IL28B rs12979860 SNP found among the Pakistani HCV patients as predictive markers for the efficiency of (IFN + ribavirin) combinational therapy. The results of this study were found consistent with the study published recently, which reports that IL28B contributes to viral resistance and is known to be up regulated as a result of interferons and RNA virus infection .…”
Section: Discussionsupporting
confidence: 59%
“…The strongest association, among a predominantly caucasian population, was noted for the rs12979860 SNP where the CCrs12979860, had 2‐fold increased likelihood of achieving SVR as compared to the TT variant . However, in a recently published study from Pakistan, a significant association of HCV genotypes and genetic variants of IFNL (IL28B) have been shown with IFN α + Rib treatment of HCV infection .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is noteworthy that PCR-RFLP assay has been utilized to determine this polymorphism in several studies such as those conducted by Sharafi et al (23), Irman et al (24), Fateh et al (16), and Nakamoto et al (25). These studies have reported that this assay is simple, fast, inexpensive, and valid.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-based confi rmation of HCV RNA was performed in ASAB diagnostic laboratories. Th e quantifi cation of HCV RNA was carried out by real time PCR according to the manufacturer's protocol using Applied Biosciences 7300 Real time PCR System (Imran et al, 2015). Th e samples were run in parallel along with the quantifi cation standards (synthetic internal controls).…”
Section: Methodsmentioning
confidence: 99%